Site index - The Editors, - (Nordic Archaeological Abstracts - NAA, 2003)
The specific names of sites are listed for castles, churches, monasteries, towns, and well-known find localities. The name of the relevant country, district, or region according to the maps is always listed, except when the paper deals with a larger area. Regional names introduced later than 1974 are marked with * and are thus not used in all volumes of NAA. General surveys may be found under SURVEY in the Subject index. Outside the Nordic area, the name of the country is listed, as are well-known find localities and sites. A guide to the alphabetical arder is given in the Author index